Arteriosclerosis, Atherosclerosis, and Cardiovascular Health: Joint Relations to the Incidence of Cardiovascular Disease. Issue 5 (4th October 2021) - Vasan, Ramachandran S.; Pan, Stephanie; Larson, Martin G.; Mitchell, Gary F.; Xanthakis, Vanessa
Abstract : Supplemental Digital Content is available in the text. Abstract : Aging is associated with an increased prevalence of subclinical atherosclerosis and stiffening of the arterial walls (arteriosclerosis). These 2 coexisting conditions are mitigated by the presence of ideal cardiovascular health (optimal levels of fasting blood glucose, cholesterol, resting blood pressure, body mass index, no smoking, good dietary quality, and regular physical activity). We hypothesized that the concomitant presence of subclinical atherosclerosis (coronary artery calcification), arteriosclerosis (higher carotid-femoral pulse wave velocity), and suboptimal cardiovascular health is associated with increased risk of cardiovascular disease relative to the absence of these 3 conditions. We tested our hypothesis in the community-based Framingham Heart Study cohort (N=2580, mean age 52 years, 49% women). We classified participants based on (1) the presence versus absence of coronary artery calcium; (2) higher (>sex-specific median) carotid-femoral pulse wave velocity; (3) poor cardiovascular health (score 0–7). Thus, participants could have no abnormalities (referent group), 1, 2, or 3 suboptimal measures. We used Cox regression to relate the number of suboptimal measures (0–3) to the incidence of cardiovascular disease during follow-up (median 14 years). Cardiovascular disease incidence rates/1000 person-years in groups with 0 to 3 suboptimal measures were 1.93 (95% CI, 1.28–2.90), 4.68 (95% CI, 3.48–6.29), 8.93 (95% CI, 6.99–11.41), and 18.26 (95% CI, 14.65–22.77), respectively. Compared with the group with no abnormalities, corresponding multivariable-adjusted hazards ratios for cardiovascular disease were 1.81, 2.18, and 3.71, respectively ( P <0.05 for all). Our observations suggest that the conjoint presence of atherosclerosis, arteriosclerosis, and poor cardiovascular health substantially elevates cardiovascular disease risk, whereas their absence denotes low risk.